Konsep Dasar Kebijakan Pendidikan - Al Fittoh, Krisna Rasyid; Ayun, Anisa Qurrata’; Mustika Aji, Lintang Ahmad (PT. Cahya Edupreneur Indonesia, 2023)
Education policy is an important matter in the process of achieving national education goals so that an understanding of the basic concepts of education policy is needed in order to produce educational policies that are proactive and problem solving. The purpose of writing this article is to study the scope of education policy which consists of the definition of education policy, components of education policy, implementation of education policy and objectives of education policy. This writing methodology uses a literature study methodology. This article was written by reviewing 12 journals related to education policy. The results of the study found that educational policy is a policy related to the field of education in the process of elaborating the vision and mission of education to achieve educational goals through strategic steps in implementing education. The education policy has the character of its own goals which include having instructive goals, having a proper point of view, having operational ideas, being made by experts, being able to be assessed clearly, and having a systematic approach. pecifically to carry out intending to achieve something